Millimeter-wave study of London penetration depth temperature dependence in Ba(Fe₀.₉₂₆Co₀.₀₇₄)₂As₂ single crystal - Barannik, A.A.; Cherpak, N.T.; Ni, N.; Tanatar, M.A.; Vitusevich, S.A.; Skresanov, V.N.; Canfield, P.C.; Prozorov, R.; Glamazdin, V.V.; Torokhtii, K.I. (Физика низких температур, 2011)
In-plane surface Ka-band microwave impedance of optimally doped single crystals of the Fe-based superconductor Ba(Fe₀.₉₂₆Co₀.₀₇₄)₂As₂ (Tc = 22.8 K) was measured. Sensitive sapphire disk quasi-optical resonator with high-Tc cuprate conducting endplates was developed specially for Fe-pnictide superconductors. It allowed finding temperature variation of London penetration depth in a form of power law, namely Δλ(T) ∼ Tn with n = 2.8 from low temperatures up to at least 0.6Tc consisted with radio-frequency measurements. This exponent points towards nodeless state with pairbreaking scattering, which can support one of the extended s-pairing symmetries. The dependence λ(T) at low temperatures is well described by one superconducting small-gap (Δ ≅ 0.75 in kTc units, where k is Boltzman coefficient) exponential dependence.